Global Warming Potential: A Brief Guide to Understanding and Evolving - Jawad, Nida (Journal of Peace, Development and Communication, 2022)
Nowadays there is a serious concern about Global Climate Change. Most of people are still ignorant of global warming and do not consider it to be a big problem in years to come. It is a complicated issue full of worries and arguments. Constantly Fossil fuels are being used to produce electricity. Deforestation is also a reason for rise in temperatures. In this article, the major causes and consequences of global warming have been reviewed and discussed to educate non-technical readers. Human activities that lead to the GW like deforestation, burning of fossil fuels, etc are briefly described. Moreover, the effects of GW such as temperature increase, rising seawater level, and heatwave threats, have also been discussed.